Hiduik Mamakai and Early Marriage: A Means of Gender Identity for Gambir Peasant Women - Jelly, Jelly; Yulkardi, Yulkardi; Yunarti, Yunarti (Universitas Negeri Medan, 2024)
We want to explain about the lifestyle philosophy of